Electrodeposited Fe on Cu foam as advanced fenton reagent for catalytic mineralization of methyl orange - Vainoris, Modestas; Nicolenco, Aliona; Tsyntsaru, Natalia; Podlaha-Murphy, Elizabeth; Alcaide, Francisco; Cesiulis, Henrikas (Frontiers in Chemistry, 2022)
In many countries, the textile industry remains the major contributor to environmental pollution. Untreated textile dyes discharged into water negatively impact the performance of aquatic organisms and may cause a variety of serious problems to their predators. Effective wastewater treatment is a key to reducing environmental and human health risks. In this work, the Fe/Cu catalysts were used in heterogeneous Fenton’s reaction for the degradation of high concentrations of methyl orange (model azo dye) in aqueous solutions. For the first time, the catalysts were prepared onto commercial copper foams by potentiostatic electrodeposition of iron using an environmentally friendly electrolyte. The influence of electrodeposition conditions, H2O2 concentration, dye concentration and temperature on the model dye degradation was investigated. It was revealed that both the surface area and the catalyst loading play the major role in the effective dye degradation. The experimental results involving spectrophotometric measurements coupled with total carbon and nitrogen quantification suggest that a solution containing up to 100 mg/L of methyl orange can be successfully decolorized within 90 s at 50°C using porous Fe/Cu catalyst in the presence of hydrogen peroxide that largely surpasses the current state-of-the-art performance. Already within the first 10°min, ∼ 30% of total methyl orange concentration is fully mineralized. The described process represents a cost-efficient and environmentally friendly way to treat azo dyes in aqueous solutions.